Meredith Monk: art in the boundaries between languages - Agostini Storolli, Wania Mara [UNESP] (Univ Estado Santa Catarina-udesc, 2017)
This article is about Meredith Monk's artistic production, which transcends traditional categories, specially focusing on Juice - a theater-cantata in three installments of 1969. Based on considerations on the structure and presentation of this work, the study looks at the various aspects that place this production in the context of the emergence of new forms of artistic expression in the last decades of the twentieth century, such as the relativization of traditional categories, performance in unconventional spaces, the use of architecture as structure, the mixing of languages and the proposal of new forms of perception.
Keywords: Meredith Monk; performance; multimedia art; installation